STAPHYLOCOCCUS, STIMULATORS OF GROWTH FOR RAPID DIAGNOSIS OF HEALTHCARE-ASSOCIATED INFECTIONS - N. F. Kryukova; S. N. Adamovich; A. N. Mirskova; E. V. Anganova (Acta Biomedica Scientifica)
The possibility of using biologically active proton (2-hydroxyethyl) ammonium, ionic liquids of the general formula HN+RiR2(CH2CH2OH)3_n.•OOCCH,X(Ind)Ai; R = H, Me, X = O, S, SO; n = 0-2 as stimulators of growth S. aureus shows in the article. 24 strains isolated from patients with purulent-septic complications from the surgical department studied. There are shown a significant acceleration, of growth of S. aureus in a agar nutrient containing yolk-salt agar, the addition of stimulants tested at concentrations 4.10-6.10 wt. %. Proposed use of stimulants for the development of improved methods of rapid diagnosis of healthcare-associated infections caused by S. aureus, which will greatly reduce the time of issue analysis and. prescribe adequate treatment promptly sick.